2010
DOI: 10.3109/00952991003592311
|View full text |Cite
|
Sign up to set email alerts
|

Risk Practices Associated with Bacterial Infections among Injection Drug Users in Denver, Colorado

Abstract: Background There has been limited research on bacterial infections (e.g., skin and soft tissue abscesses, endocarditis) among injection drug users (IDUs), despite these infections often resulting in serious morbidity and costly medical care. Although high-risk practices that contribute to bacterial infections are not entirely clear, certain injection practices have been found to increase risk in past studies. Objectives To examine rates of bacterial infections among IDUs in Denver, CO and high-risk practices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
99
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(107 citation statements)
references
References 21 publications
5
99
3
Order By: Relevance
“…The frequency of abscess infections in the present sample was comparable to the 29% frequency reported for injection drug users in Colorado, USA in 2010 [5]. Injection frequency, puncture site and the prevalence of other infections, such as hepatitis C and…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The frequency of abscess infections in the present sample was comparable to the 29% frequency reported for injection drug users in Colorado, USA in 2010 [5]. Injection frequency, puncture site and the prevalence of other infections, such as hepatitis C and…”
Section: Discussionsupporting
confidence: 75%
“…A higher infectious rate also increases nutritional needs, and insufficient dietary intakes promote malnutrition and co-morbidities, suppress immune function and diminish response to therapies [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in San Francisco, California, a study found that 54 (32%) of 169 IDUs in one neighborhood had current abscesses, cellulitis, or both during a physical examination (Binswanger, Kral, Bluthenthal, Rybold, & Edlin, 2000). In Vancouver, Canada, and Tijuana, Mexico, studies reported that ~20% of IDUs had an abscess in the prior 6 months (Lloyd-Smith et al, 2005; Pollini et al, 2010); in Denver, Colorado, 29% of IDUs reported an abscess in the prior year (Phillips & Stein, 2010). Abscesses can be very painful and prompt treatment, mostly with antibotics, may succeed in avoiding more costly and invasive surgical incision and drainage of abscess wounds.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, intravenous drug users are more at risk (10% of IE) due to poor hygiene. Indeed 55% of active heroin, cocaine and methamphetamine injection drug users report a lifetime history of skin infection mainly in cases of intramuscular injection or frequent heroin or speedball injection (Phillips, 2010). In these cases, S. aureus and fungi must be suspected and treated.…”
Section: Situations At Riskmentioning
confidence: 99%